2020
DOI: 10.7196/samj.2020.v110i2.13823
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care CD4+ technology implementation in Free State, South Africa, was associated with improved patient health outcomes

Abstract: CD4+ testing is the most predictable indicator of HIV disease progression, and owing to limited resources is widely used to determine whether a patient is eligible for antiretroviral therapy (ART). Currently, in settings where it is available, CD4+ testing is used to determine whether a patient is eligible for ART, and it is more reliable in determining ART eligibility than symptomatic staging. [1,2] Patients who do not have reliable on-site access to testing must often make numerous visits to healthcare facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…The findings indicated a good consistency and relevance between POC devices and flow cytometry test results with correlation coefficients >0.8. Moreover, the consistency was also close to the results reported in other research (11,(13)(14). This study did find variations in the CD4 cell counts test results for the same PLWH samples from different laboratories using POC devices and flow cytometers.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The findings indicated a good consistency and relevance between POC devices and flow cytometry test results with correlation coefficients >0.8. Moreover, the consistency was also close to the results reported in other research (11,(13)(14). This study did find variations in the CD4 cell counts test results for the same PLWH samples from different laboratories using POC devices and flow cytometers.…”
Section: Discussionsupporting
confidence: 91%
“…In some countries, studies have shown that adopting POC CD4 detection instruments can meaningfully improve the timeliness of initiating antiviral therapies (6,(11)(12). Timeliness plays a vital role in the care and therapeutic evaluation of HIV patients; this is especially witnessed in mobile HIV testing services (HTS) delivery, which patients are often more willing to use (11). Therefore, using POC CD4 cell detectors, based on their accuracy and reliability, for PLWH in districts or counties without high-standard laboratories is a novel strategy in HIV prevention and control work that will help promote detection accessibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 21 ] A recent study among 1053 venous samples from Botswana demonstrated 94% (112/119) sensitivity compared to flow cytometry but positive predictive value for CD4 <200 cells/mm [ 3 ] was only 46% [ 22 ]. If the goal is to identify and screen persons at highest risk of undiagnosed OIs, false-positive results may be a reasonable trade-off for a highly sensitive POC test that can allow for rapid OI screening prior to ART initiation [ 23 ]. One additional drawback is that healthcare workers often prefer a precise CD4 value over a semiquantitative CD4 range [ 24 , 21 ].…”
Section: Identification Of People With Ahd: Cd4 Testing As the Gatewa...mentioning
confidence: 99%